2006
DOI: 10.1016/j.jde.2006.01.013
|View full text |Cite
|
Sign up to set email alerts
|

A diffusive predator–prey model with a protection zone

Abstract: In this paper we study the effects of a protection zone Ω 0 for the prey on a diffusive predator-prey model with Holling type II response and no-flux boundary condition. We show the existence of a critical patch size described by the principal eigenvalue λ D 1 (Ω 0 ) of the Laplacian operator over Ω 0 with homogeneous Dirichlet boundary conditions. If the protection zone is over the critical patch size, i.e., if λ D 1 (Ω 0 ) is less than the prey growth rate, then the dynamics of the model is fundamentally cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(90 citation statements)
references
References 43 publications
3
84
1
2
Order By: Relevance
“…See [7,11] and references therein for the stability of prey-predator model incorporating prey refuge. Du and Shi studied the effect of a protection zone in the diffusive Holling type II functional response prey-predator model in [40]. In [29,35,37], authors discussed the stability analysis of prey-predator model with Holling type II functional response in a two patch environment: one accessible to both prey and predator (patch 1) and the other one being a refuge for the prey (patch 2).…”
Section: Introductionmentioning
confidence: 99%
“…See [7,11] and references therein for the stability of prey-predator model incorporating prey refuge. Du and Shi studied the effect of a protection zone in the diffusive Holling type II functional response prey-predator model in [40]. In [29,35,37], authors discussed the stability analysis of prey-predator model with Holling type II functional response in a two patch environment: one accessible to both prey and predator (patch 1) and the other one being a refuge for the prey (patch 2).…”
Section: Introductionmentioning
confidence: 99%
“…It may be noted here that under conditions (9) or (10), both the predator and prey species coexist, and they settle down at its equilibrium level.…”
Section: Theoremmentioning
confidence: 86%
“…Grieco et al [12] developed a hybrid numerical approach to study the transport processes in the GON and applied it to the dispersion of zooplankton and phytoplankton population dynamics. Du and Shi [9] studied the effects of a protection zone for the prey on a diffusive predator-prey model with Holling type II response and no-flux boundary condition. Ko and Ryu [14,15] investigated the existence and non-existence of non-constant positive steady-states of a diffusive predator-prey interaction system under homogeneous Neumann boundary condition and observed that the monotonicity of a prey isocline at the positive constant solution plays an important role.…”
Section: Introductionmentioning
confidence: 99%
“…To conclude the paper, we discuss the stability of the unique positive solution when n = 1 by estimating the eigenvalues of the linearized equation. Similar arguments have been used in, for example, [14,28]. The local stability of the unique positive solution of (P ) k is important for a better understanding of the dynamics of the original reaction-diffusion system (1.2) when p = 1 and n = 1, but it is a challenging question in general.…”
Section: ) Then (0 0) Is the Unique Solution Of (42)mentioning
confidence: 93%